Impacts of future climate and agricultural land‐use changes on regional agricultural water use in a large irrigation district of northwest China. (11th March 2019) - Sun, Shikun; Zhou, Tianwa; Wu, Pute; Wang, Yubao; Zhao, Xining; Yin, Yali
Abstract: Agricultural sectors are facing various environmental threats, such as land degradation and water resource depletion. Agricultural water use and cropping patterns are closely linked to each other, with both related to the regional climate. This study evaluated the impacts of future climate and agricultural land‐use changes on agricultural water consumption in the Hetao Irrigation District (HID), China. The results show that owing to an increase in temperature and a decrease in precipitation, the future climate in the research area will become warmer and dryer, which will increase the water demand of crops. Future climate in the HID will lead to a 10.5% increase in total irrigation water demand under a scenario of high greenhouse gas emissions and a 6.9% increase under a scenario of low greenhouse gas emissions. Results of the grey prediction modeling indicate that the amount of water allocated to the agricultural sector will decrease, which will make it difficult to meet crop irrigation demands. The results of the gray model also show that the cropping pattern in the HID will vary over time, and the proportion of the area of cash crops will increase by 5.3% during the next decade. Regional agricultural water use can be reduced by adjusting the cropping pattern under irrigation water limitations. Meanwhile, the saved water can be used for soil desalination in cultivated land in the HID. Consequently, adjusting the cropping pattern is a nature‐based solution by which to address climate change and guarantee the sustainable use of regional water and land resources.